Phenomenal justice : violence and morality in Argentina - Van Roekel, Eva, 1981- (Genocide, political violence, human rights series., 2020)
"How do victims and perpetrators of political violence caught up in a complicated legal battle experience justice on their own terms? Phenomenal Justice is a compelling ethnography about the reopened trials for crimes against humanity committed during the brutal military dictatorship that ruled Argentina between 1976 and 1983. Grounded in phenomenological anthropology and the anthropology of emotion, this book establishes a new theoretical basis that is faithful to the uncertainties of justice and truth in the aftermath of human rights violations. The ethnographic observations and the first-person stories about torture, survival, disappearance, and death reveal the enduring trauma, heartfelt guilt, happiness, battered pride, and scratchy shame that demonstrate the unreserved complexities of truth and justice in post-conflict societies. Phenomenal Justice will be an indispensable contribution to a better understanding of the military dictatorship in Argentina and its aftermath."--